Increasing The Quality Of Conditioning Cross Voltage In The Lb10 Network Voltage Drop In The Work Area Of PT PLN (Persero) ULP Labuhan Haji - Nail Fadhlan; Solly Aryza; Siti Anisah (INFOKUM, 2021)
Upgrade network conductors to reduce voltage drop to improve service quality and reduce the effects of power loss. The system voltage is distributed to the network at a voltage of 380/220 volts and then to the residents' apartments. Due to the load supply from a single-phase system, this unbalanced load condition eventually causes current to flow in the neutral phase (leakage current) and to ground. The simulation was carried out using the tidal analysis method from the ETAP (Electric Transient and Analysis Program) 16.0 application. The voltage drop on the power grid affects the quality of the operating voltage received from the power company. If the voltage drop is not in accordance with the standard (SPLN No. 1 of 1995), the quality of the operating voltage may decrease and power loss may occur. If the state of the system is truly in a state of equilibrium, the existing power losses will only occur on the R, S, and T channels. To find power losses in a 380 V voltage network, it is necessary to know or determine the impedance, phase, and current. neutral and look for power losses in the load. Therefore, to overcome the power losses from unbalanced loads, the load balancing method is used. Based on engineering and measurement data, simulations were carried out to obtain standard compliance results for operating voltage quality and reduce voltage drop effects. Increasing the cross-sectional size of the conductor improves the simulation of the electrical aspect. To find power losses on a 380 V voltage network, it is necessary to know or determine the impedance, phase, and neutral current and look for power losses in the load.